Dose-dependent transduction of Hedgehog relies on phosphorylation-based feedback between the G-protein-coupled receptor Smoothened and the kinase Fused. - Sanial, M.; Bécam, I.; Hofmann, L.; Behague, J.; Argüelles, C.; Gourhand, V.; Bruzzone, L.; Holmgren, R.A.; Plessis, A. (Development, 2017)
Smoothened (SMO) is a G-protein-coupled receptor-related protein required for the transduction of Hedgehog (HH). The HH gradient leads to graded phosphorylation of SMO, mainly by the PKA and CKI kinases. How thresholds in HH morphogen regulate SMO to promote switch-like transcriptional responses is a central unsolved issue. Using the wing imaginal disc model in Drosophila, we identified new SMO phosphosites that enhance the effects of the PKA/CKI kinases on SMO accumulation, its localization at the plasma membrane and its activity. Surprisingly, phosphorylation at these sites is induced by the kinase Fused (FU), a known downstream effector of SMO. In turn, activation of SMO induces FU to act on its downstream targets. Overall, our data provide evidence for a SMO/FU positive regulatory loop nested within a multikinase phosphorylation cascade. We propose that this complex interplay amplifies signaling above a threshold that allows high HH signaling.